Factors influencing resilience in patients with burns during rehabilitation period - Zhen Yang; Jun-qiao Wang; Bao-zhen Zhang; Yu Zeng; Hai-ping Ma (Elsevier, 2014)
Purpose: To investigate the factors that influence levels of resilience in patients with burns during rehabilitation, and to provide theoretical guidance for psychological crisis prevention and intervention. Methods: A total of 129 patients with burns and undergoing rehabilitation were investigated using a demographic questionnaire, the Connor-Davidson Resilience Scale (CD-RISC), the Social Support Rating Scale (SSRS), and the Simplified Coping Styles Questionnaire. Results: The overall resilience score of burn patients was at a middle level. Multiple regression analysis showed that gender, marital status, occupation, educational level, burn severity, and a positive coping style were all significant factors influencing patient resilience. Conclusion: During psychological crisis intervention, medical staff should guide burn patients according to their individual coping styles. Such guidance would achieve a better effect, improve patient resilience, and promote positive psychological adaptation.